Analyses of the plastic deformation of coated conductors deconstructed from ultra-high field test coils. (12th August 2020) - Hu, Xinbo; Small, Michael; Kim, Kwanglok; Kim, Kwangmin; Bhattarai, Kabindra; Polyanskii, Anatolii; Radcliff, Kyle; Jaroszynski, Jan; Bong, Uijong; Park, Jeong Hwan; Hahn, Seungyong; Larbalestier, David
Abstract: REBCO coated conductors are now being used for building very high-field magnets with large electromagnetic stresses, both expected ones due to transport current J ⃗ × B ⃗ stresses and additional stresses resulting from the large screening currents inherent in wide tapes. Post mortem analyses of several recent test coils operated above 40 T show that significant conductor plastic deformation occurs, even for JBR stresses well below the ∼1 GPa yield of the Hastelloy substrate of the conductor. To investigate these deformation mechanisms, conductors were unwound after coil test and carefully examined with respect to their length-wise Ic which revealed many areas of local damage. Regions of interest were examined by metallographic cross-section, Hall microscopy, magneto-optic imaging and scanning electronic microscopy. Important damage frequently occurred to the outer edges of pancakes in the coil ends, which were often plastically deformed over the whole turn circumference, especially when this outer edge was a slit edge. Internal conductor damage was also seen, especially delamination between the buffer and REBCO layers at slit edges. Careful sectioning of the tape at ∼10 mm intervals showed that the plastic deformation of the turns was complex and variable around the turn circumference, with tape cross-sections that exhibited continuous shape change in the outer turns. The bending center line of tapes often shifted from the tape center line toward the edge closest to the coil center, indicating asymmetric effects of transport and screening current stresses across the conductor width. A surprising and vital result is that damage was prevalent when the slit edge was also the edge at which transport current flowed. This damage was absent when the transport current flowed at the not-slit edge, implying great sensitivity of the effect of screening current stresses to localized conductor damage.